Ampliando as dimens\~oes de indicadores compostos municipais: A inclus\~ao da dinâmica econômica - Bruno Cruz; Carlos Wagner de Albuquerque Oliveira; Paulo Furtado de Castro; Pedro H. M. Albuquerque (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The aims of this paper is to construct indicators that can help economic agents to know the generals aspects of each county in terms of human development characteristics, economic development, fiscal development, banking development and economic dynamism. From these indicators, we seek to create typologies of homogeneous counties behind of socio-economic characteristics. This paper also take discussion about the empirical regularity of distribution of cities concerned of it's size. This distribution is known in the literature as Zipf's Law. We take some empirical evidence for the Brazilian case. We show how to build composite index to present and justify the use of technical statistical principal components. Them, it is show the construction of the indicators, the main object of this paper. The general index is made from six partial indices. We also made the grade of Brazilian counties and their rank. Finally, here are some of the conclusions of the work.
Keywords: O18; C43; 330